1980
DOI: 10.1007/bf00006565
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relationship between aquatic insect growth and water temperature in a small stream

Abstract: The growth of aquatic insects in a small mountain stream was studied with emphasis on water temperature. Growth of the five dominant species was examined in relation to degree-days. This measure accounts for time and the minimum temperature necessary for insect growth. All species showed reduced specific growth rates with lower temperatures, but some (Ephemerella dorothea, Leuctra tenella, Nemoura wui) did not stop growing at even the lowest water temperatures. Both Diplectrona modesta and Paraleptophlebia ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…The relationship between size and water temperature in aquatic insects is complex, and a number of hypotheses have been proposed to explain this relation- ship (Ray 1960, Sweeney and Vannote 1978, Vannote and Sweeney 1980, Hawkins 1986, Hogue and Hawkins 1991. Some researchers have observed that aquatic insects within the same stage of development from high-altitude, colder sites were smaller (Anderson and Cummins 1979, Markarian 1980, Wise 1980, Rader and Ward 1990, whereas others have noted insects from colder streams were larger (Hogue and Hawkins 1991). Our preliminary research has shown that some taxa from LBC (high altitude) were smaller than those from SFP (low altitude).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between size and water temperature in aquatic insects is complex, and a number of hypotheses have been proposed to explain this relation- ship (Ray 1960, Sweeney and Vannote 1978, Vannote and Sweeney 1980, Hawkins 1986, Hogue and Hawkins 1991. Some researchers have observed that aquatic insects within the same stage of development from high-altitude, colder sites were smaller (Anderson and Cummins 1979, Markarian 1980, Wise 1980, Rader and Ward 1990, whereas others have noted insects from colder streams were larger (Hogue and Hawkins 1991). Our preliminary research has shown that some taxa from LBC (high altitude) were smaller than those from SFP (low altitude).…”
Section: Discussionmentioning
confidence: 99%
“…Life history and population genetics are two possible factors that may contribute to the differential sensitivity of the same aquatic insect species to chemical contaminants (Poff and Ward 1990). Life history traits may be important because individuals from a high-altitude stream may be smaller than individuals of the same species from a lower altitude stream within the same lifestage (Markarian 1980, Wise 1980, Rader and Ward 1990, although the opposite trend has also been observed (Hogue and Hawkins 1991). Regardless, it has been shown that smaller individuals of aquatic insects are more sensitive to contaminants than larger individuals of the same species (Powlesland and George 1986, Diamond et a!.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the parameters reflecting the thermal demand of the species throughout their development period, such as degreedays and other parameters based on means, seemed to correlate best with the species distribution. Several studies have tested the influence of degree-days on development or distribution of benthic macroinvertebrate species and found strong correlations or directly proportional growth rates (Markarian 1980;Lowe and Hauer 1999;Watanabe et al 1999;Knispel et al 2006). Other studies underline the importance of temperature maxima for species growth and distribution (Jacobsen et al 1997;Lowe and Hauer 1999;Sponseller et al 2001).…”
Section: Relative Importance Of Thermal Parameters For Macroinvertebrmentioning
confidence: 95%
“…Water temperature plays an important role in determining mortality, growth rate, fecundity, survival, and distribution of aquatic invertebrates (e .g . Brittain, 1983 ;Markarian, 1980 ;Olsson, 1981 ;Soderstrom, 1988 ;Vannote, 1978 ;Williams & Hynes, 1974) .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of thermal units (e .g . degree-days) above a threshold (Markarian, 1980) and the rate of temperature increase in the spring or the rate of temperature decrease in the autumn (Ward & Stanford, 1982) may also be important to stream insects .…”
Section: Introductionmentioning
confidence: 99%